Beta adrenoceptor blockade ameliorates impaired glucose tolerance and alterations of the cerebral ceramide metabolism in an experimental model of ischemic stroke. (17th April 2018) - Luger, Sebastian; Schwebler, Annette; Vutukuri, Rajkumar; Bouzas, Nerea Ferreiros; Labocha, Sandra; Schreiber, Yannick; Brunkhorst, Robert; Steinmetz, Helmuth; Pfeilschifter, Josef; Pfeilschifter, Waltraud
Background: Sphingolipids are versatile signaling molecules derived from membrane lipids of eukaryotic cells. Ceramides regulate cellular processes such as proliferation, differentiation and apoptosis and are involved in cellular stress responses. Experimental evidence suggests a pivotal role of sphingolipids in the pathogenesis of cardiovascular diseases, including ischemic stroke. A neuroprotective effect has been shown for beta-adrenergic antagonists in rodent stroke models and supported by observational clinical data. However, the exact underlying pathophysiological mechanisms are still under investigation. We aimed to examine the influence of propranolol on the ceramide metabolism in the stroke-affected brain. Methods: Mice were subjected to 60 or 180 min transient middle cerebral artery occlusion (tMCAO) and infarct size, functional neurological deficits, glucose tolerance, and brain ceramide levels were assessed after 12, 24, and 72 h to evaluate whether the latter two processes occur in a similar time frame. Next, we assessed the effects of propranolol (10 mg/kg bw) at 0, 4 and 8 h after tMCAO and FTY720 (fingolimod; 1 mg/kg) on infarct size, functional outcome, immune cell counts and brain ceramide levels at 24 h after 60 min tMCAO. Results: We found a temporal coincidence between stroke-associated impaired glucose tolerance and brain ceramide accumulation. Whereas propranolol reduced ischemic lesion size, improved functional outcome and reduced brain ceramide accumulation without an effect on circulating immune cells, FTY720 showed the known neuroprotective effect and strong reduction of circulating immune cells without affecting brain ceramide accumulation. Conclusions: Propranolol ameliorates both stroke-associated impairment of glucose tolerance and brain ceramide accumulation which are temporally linked, strengthening the evidence for a role of the sympathetic nervous system in regulating post-stroke glucose metabolism and its metabolic consequences in the brain.